ANALISIS KEBIJAKAN MADRASAH BERBASIS ASRAMA TERHADAP PEMBENTUKAN KARAKTER SISWA DI MAN PURWOREJO - Iyus Herdiana Saputra; Rofiq Nurhadi; Ari Fajar Isbakhi; herdiana saputra, iyus (AL-MUADDIB: Jurnal Kajian Ilmu Kependidikan, 2026)
This study aims to analyze the dormitory-based madrasah policy at Madrasah Aliyah Negeri (MAN) Purworejo and its influence on the formation of student character. This research is motivated by the importance of integrated character education in the daily lives of students in a dormitory-based madrasah environment, especially in facing the challenges of the younger generation such as the influence of outside culture and various social problems. The research method used is a case study with a qualitative approach. Data was obtained through observation, interviews with madrasah managers, teachers, and students, and analysis of relevant policy documents. The results of the study show that the implementation of the dormitory-based madrasah policy at MAN Purworejo is carried out through worship habituation, discipline activities, supervision of students' daily activities, and the integration of character values in the learning process. Field findings show that the policy contributes to increasing student discipline, responsibility, independence, and compliance with madrasah rules. However, its implementation still faces obstacles in the form of limited dormitory facilities and suboptimal parental involvement in supporting student character education. The conclusion of this study shows that the dormitory-based madrasah policy at MAN Purworejo plays a role in supporting the formation of students' character through supervision and integrated coaching in daily life in the madrasah environment.